Organosilicon compound, article including substrate surface-treated with organosilicon compound, prepreg, printed wiring board, and glass cloth treatment liquid
Organosilicon compounds with specific structures enhance the mechanical and dielectric properties of substrates, addressing the limitations of existing printed wiring boards by improving adhesion and performance in high-density applications.
Patent Information
- Application Number
- JP2023121681
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing printed wiring boards face challenges in achieving improved mechanical and dielectric properties, particularly in high-density and thin-film applications, despite the use of silane coupling agents and inorganic fillers.
The use of organosilicon compounds with specific structures for surface treatment of substrates, such as silica particles and glass fibers, enhances adhesion and dielectric properties in prepregs and printed wiring boards.
The organosilicon compounds improve the mechanical and dielectric properties of prepregs and printed wiring boards, resulting in better adhesion and performance in high-density applications.
Smart Images

Figure 2025018184000001 
Figure 2025018184000002 
Figure 2025018184000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an organosilicon compound, an article including a substrate surface-treated with an organosilicon compound, a prepreg, a printed wiring board, and a glass cloth treatment liquid containing an organosilicon compound. [Background technology]
[0002] As electronic devices such as tablet terminals and smartphones become more powerful and communicate at higher speeds, the printed wiring boards used in these devices are becoming increasingly dense and extremely thin, while at the same time offering lower dielectric constants and lower dielectric loss tangents.As insulating materials for these printed wiring boards, laminates made by laminating prepregs using inorganic fillers and glass cloth as reinforcing materials for thermosetting resins such as epoxy resins and thermosetting polyphenylene ether resins (hereinafter referred to as "matrix resins") and then curing them under heat and pressure are widely used. The reinforcing materials used in these applications are surface-treated with a silane coupling agent, and the organic functional groups of the silane coupling agent react with the organic functional groups of the matrix resin, thereby improving the adhesion between the reinforcing material, such as glass cloth, and the matrix resin.
[0003] Representative silane coupling agents used in the surface treatment of glass cloth include silane coupling agents having an unsaturated double bond, such as 3-methacryloxypropyltrimethoxysilane and N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride (Patent Documents 1 and 2). In addition, inorganic fillers that have been surface-treated with a silane coupling agent having a vinyl group have been proposed, and it has been reported that resins to which such inorganic fillers have been added have improved dielectric properties, heat resistance, and moist heat resistance (Patent Document 3). However, there is still room for improvement in the dielectric properties of materials used in printed wiring boards, and further improvements in performance are desired. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2020 / 194772 [Patent Document 2] JP 2018-127747 A [Patent Document 3] Patent No. 6684822 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in view of the above circumstances, and has an object to provide an organosilicon compound that can provide an article having excellent mechanical properties and dielectric properties by surface treating the substrate of the article, and an article, prepreg, and printed wiring board that include a substrate that has been surface treated with this organosilicon compound. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems and have found that, when used in the surface treatment of a substrate for an article, an organosilicon compound having a specific structure gives an article that has excellent adhesion to the matrix resin used in the prepreg or printed wiring board, in particular, and therefore can improve the mechanical properties and dielectric properties of the prepreg or printed wiring board, thereby completing the present invention.
[0007] That is, the present invention provides 1. An organosilicon compound represented by the following formula (1): [ka] (In the formula, Me represents a methyl group, R 1 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms; R 3represents a hydrogen atom or a methyl group, X represents a p+q+1 valent hydrocarbon group having 3 to 20 carbon atoms, including a branched structure or a ring structure, m represents an integer of 1 to 3, n represents an integer of 1 to 12, p is 0 or 1, q represents an integer of 1 to 3, and p+q represents an integer of 1 to 4. 2. An organosilicon compound according to claim 1, represented by the following formula (2) or (3): [ka] (In the formula, Me, R 1 , R 2 , m and n are the same as above, and R 4 represents a hydrogen atom, a methyl group, or an allyloxy group. 3. R 1 is a hydrogen atom, a methyl group, or an ethyl group, and R 2 3. The organosilicon compound according to 1 or 2, wherein is a hydrogen atom and n is 3. 4. An article comprising a substrate surface-treated with the organosilicon compound according to any one of 1 to 3. 5. The article according to 4, wherein the substrate is an inorganic material. 6. The article according to 5, wherein the inorganic material is silica particles or glass fibers. 7. A prepreg comprising the article according to any one of 4 to 6 and a matrix resin. 8. A printed wiring board comprising the prepreg according to 7. 9. A glass cloth treatment liquid in which the organosilicon compound according to any one of 1 to 3 is dissolved in a solvent containing water. to provide. Effect of the Invention
[0008] The organosilicon compound of the present invention can be suitably used as a treating agent for inorganic fillers, glass cloth, and the like, to provide articles having excellent adhesion to resins and dielectric properties by surface treating the substrate of the article. The use of these articles makes it possible to obtain prepregs, printed wiring boards, and the like having excellent mechanical properties and dielectric properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. [Organosilicon compounds] The organosilicon compound of the present invention is an organosilicon compound represented by the following formula (1) (hereinafter, sometimes referred to as compound (1)).
[0010] [ka]
[0011] In the formula, Me represents a methyl group, R 1 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms; R 3 represents a hydrogen atom or a methyl group, X represents a p+q+1 valent hydrocarbon group having 3 to 20 carbon atoms, containing a branched structure or a ring structure, m represents an integer of 1 to 3, n represents an integer of 1 to 12, p is 0 or 1, q represents an integer of 1 to 3, and p+q represents an integer of 1 to 4.
[0012] R 1 The alkyl group having 1 to 10 carbon atoms may be linear, branched, or cyclic, and specific examples thereof include methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups. Among these, R 1 is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, even more preferably a methyl group or an ethyl group, and still more preferably a methyl group.
[0013] R 2 As the alkyl group having 1 to 10 carbon atoms, R 1Examples of the alkyl group include the same groups as those exemplified in the above, and are preferably alkyl groups having 1 to 6 carbon atoms, and more preferably alkyl groups having 1 to 3 carbon atoms. Specific examples of the aryl group having 6 to 20 carbon atoms include phenyl, α-naphthyl, and β-naphthyl groups, and are preferably aryl groups having 6 to 10 carbon atoms, and more preferably aryl groups having 6 to 8 carbon atoms. R 2 is preferably a hydrogen atom, a methyl group, or a phenyl group, more preferably a hydrogen atom or a methyl group, and even more preferably a hydrogen atom. R 3 represents a hydrogen atom or a methyl group, with a methyl group being preferred.
[0014] X represents a p+q+1 valent hydrocarbon group having 3 to 20 carbon atoms, preferably 3 to 10 carbon atoms, containing a branched structure or a ring structure, and more preferably a p+q+1 valent saturated hydrocarbon group having 3 to 6 carbon atoms, containing a branched structure. Specific examples of X include, but are not limited to, groups represented by the following formulas: In the following formulas, the wavy line represents -NR 2 The (C=O)O- oxygen atom is bonded to the aryl group, and the asterisk indicates the bond to the allyloxy, methyl, or ethyl group.
[0015] [ka]
[0016] m represents an integer of 1 to 3, preferably 2 or 3, and more preferably 3. n represents an integer of 1 to 12, and from the viewpoint of raw material procurement, an integer of 1 to 8 is preferable, an integer of 1 to 4 is more preferable, and 3 is even more preferable. p is 0 or 1. q represents an integer of 1 to 3, and is preferably 2 or 3 from the viewpoint of adhesion to the resin. p+q represents an integer of 1 to 4, preferably an integer of 1 to 3, and more preferably 2 or 3.
[0017] The organosilicon compound of the present invention is preferably one represented by the following formula (2) or (3).
[0018] [ka]
[0019] In the above formula, Me, R 1 , R 2 , m and n are the same as above, and R 4 represents a hydrogen atom, a methyl group, or an allyloxy group.
[0020] Specific examples of the compound represented by the above formula (2) include, but are not limited to, those represented by the following formulas.
[0021] [ka] (In the formula, Me represents a methyl group, and Et represents an ethyl group.)
[0022] [ka] (In the formula, Me represents a methyl group, and Et represents an ethyl group.)
[0023] Specific examples of the compound represented by the above formula (3) include, but are not limited to, those represented by the following formulas.
[0024] [ka] (In the formula, Me represents a methyl group, and Et represents an ethyl group.)
[0025] The organosilicon compound of the present invention can be produced, for example, by reacting an alkoxysilane having an isocyanato group (hereinafter sometimes referred to as "isocyanate silane") with an alcohol having an allyl group in the presence of a catalyst, but the production method is not limited to this.
[0026] Specific examples of isocyanate silanes include 3-isocyanatopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropylmethyldimethoxysilane, 3-isocyanatopropylmethyldiethoxysilane, 3-isocyanatopropylethyldimethoxysilane, and 3-isocyanatopropylethyldiethoxysilane. Specific examples of the alcohol having an allyl group include trimethylolpropane diallyl ether, pentaerythritol triallyl ether, and glycerin diallyl ether.
[0027] The reaction ratio of the isocyanate silane and the alcohol having an allyl group is preferably 0.90 mol or more and less than 1.2 mol, and more preferably 0.95 mol or more and less than 1.05 mol, of the alcohol having an allyl group per 1 mol of the isocyanate silane.
[0028] The catalyst used in the above reaction is not particularly limited, and may be a commonly used isocyanate reaction catalyst, such as a tertiary amine compound, an organic tin compound, an aluminum complex, a zirconium complex, etc., and is preferably an organic tin compound. Among them, a tin(II) carboxylate compound is more preferable from the viewpoint of catalytic activity. The amount of catalyst used is preferably 0.00001 to 1 mole, more preferably 0.0001 to 0.01 mole, per mole of isocyanate silane. If more than 1 mole is used, the effect may be saturated and it may become uneconomical. If it is less than 0.00001 mole, the catalytic effect may be insufficient, the reaction rate may be low, and the productivity may decrease.
[0029] When a catalyst is used in the above reaction, a step of removing or reducing the amount of the catalyst may be carried out. The removal method is not particularly limited, but examples thereof include a method of distillation under reduced pressure for a low-boiling tertiary amine compound, and a method of adsorption and removal using inorganic oxides such as silicon oxide, magnesium oxide, and aluminum oxide for an organotin compound. When an adsorption and removal step using an inorganic oxide is carried out, the inorganic oxide can be removed by filtration in a subsequent step.
[0030] In the production of the organosilicon compound of the present invention, a solvent may be used if necessary.The solvent is not particularly limited as long as it is non-reactive with the raw material isocyanate silane and the alcohol having an allyl group, and specifically includes aliphatic hydrocarbon solvents such as pentane, hexane, heptane, decane, etc.; ether solvents such as diethyl ether, tetrahydrofuran, 1,4-dioxane, etc.; amide solvents such as formamide, dimethylformamide, N-methylpyrrolidone, etc.; aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc.
[0031] In the production of the organosilicon compound of the present invention, the reaction is an exothermic reaction, and therefore, from the viewpoints of productivity and suppression of side reactions, the reaction temperature is preferably 20 to 150°C, more preferably 30 to 130°C, and even more preferably 40 to 110°C. The reaction time is not particularly limited, but is preferably from 10 minutes to 24 hours, and more preferably from about 1 hour to 10 hours.
[0032] [Goods] The article of the present invention comprises a substrate that has been surface treated with the organosilicon compound described above. (1) Organosilicon compounds The organosilicon compound used in the article of the present invention is represented by the above formula (1). Specific examples and preferred examples of the organosilicon compound are as described above. The organosilicon compound of the present invention is applied to the surface of a substrate, and then heated and dried to obtain a substrate surface-treated with the organosilicon compound of the present invention.
[0033] (2) Base material The substrate is not particularly limited, but inorganic materials are preferred, and specific examples thereof include inorganic particles (inorganic fillers) such as silica, titania, zirconia, calcium carbonate, magnesium carbonate, alumina, magnesium oxide, aluminum hydroxide, magnesium hydroxide, talc, clay, and mica; glass fibers such as monofilaments, glass strands, glass yarns, glass rovings, twisted yarns, bulky processed yarns, chopped strands, milled fibers, staple fibers, glass cloths, nonwoven fabrics, tapes, and nets; ceramics such as porcelain, cement, enamel, and fine ceramics; and metals such as iron, aluminum, copper, silver, gold, and magnesium. Among these, silica particles or glass fibers are particularly preferred from the viewpoint of the reactivity of the alkoxysilyl group.
[0034] (2-1) Silica particles The silica particles are not particularly limited, and examples thereof include colloidal silica, fumed silica, crystalline silica, and fused silica. In the case of colloidal silica, the silica particles are preferably colloidally dispersed in a medium such as water or an organic solvent, and commercially available water-dispersed or organic-dispersed types can be used. The shape of the silica particles is not particularly limited, and examples thereof include spherical and irregular shapes, but spherical shapes are preferred, and the average particle size is also not particularly limited, but a median size measured by dynamic light scattering is preferably 1 to 100 nm. As such silica particles, commercially available products can be used, and examples thereof include Snowtex O, OS, O40, OL, methanol silica sol, IPA-ST, IBA-ST, PMA-ST, MEK-ST, and the like manufactured by Nissan Chemical Industries, Ltd. Among these, Snowtex O is preferred.
[0035] (2-2) Glass fiber As the glass fiber, glass cloth is preferred. The glass yarn constituting the glass cloth that is the substrate before surface treatment is not particularly limited, and glass compositions of known glass compositions can be used. Specific examples thereof include E glass, L glass, L2 glass, NE glass, NE2 glass, S glass, T glass, UT glass, LU glass, D glass, silica glass, etc., and one or more types of glass cloth selected from the group consisting of these glasses are used depending on the application. Among these, glass cloth selected from L glass, L2 glass, NE glass, NE2 glass, LU glass, and silica glass is preferred in terms of dielectric properties. In the present invention, the dielectric loss tangent at 10 GHz refers to a value measured by the method described in JIS R 1641:2007 (Method for measuring microwave dielectric properties of fine ceramic substrates).
[0036] It is preferable to remove organic substances such as a sizing agent attached to the surface of the glass cloth before surface treatment with the organosilicon compound, since the surface of the glass cloth can be treated evenly with the organosilicon compound. Methods for removing the organic substances include heat cleaning treatment, corona treatment, and hot water washing treatment.
[0037] The thickness of the glass cloth is preferably 6 to 200 μm, more preferably 10 to 100 μm, and the mass per unit area is preferably 5 to 200 g / m 2 and 10 to 100 g / m 2 The glass cloth is more preferable.
[0038] (3) Manufacturing method of the article The article of the present invention includes a substrate that has been surface-treated as described above. It is preferable that the surface-treated substrate itself is used as the article. In this case, the method for producing the article of the present invention is not particularly limited, and the article of the present invention can be produced by appropriately selecting a surface treatment method for the substrate depending on the type, shape, etc. of the substrate.
[0039] (3-1) Method for producing surface-treated silica particles When silica particles are used as the substrate, for example, a method of surface treatment in a solvent may be used. When a resin is used in a post-process, a kneading treatment in which compound (1) is added to and mixed with a compound consisting of untreated silica particles and a resin dispersion medium may be used. However, the method of surface treatment in a solvent is preferred. The solvent may be one that is generally easily available, and examples thereof include water; alcohol-based solvents such as methanol, ethanol, and isopropyl alcohol; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; hydrocarbon-based solvents such as hexane, toluene, and xylene; ether-based solvents such as diethyl ether, tetrahydrofuran, and dioxane; and ester-based solvents such as ethyl acetate and butyl acetate. One type of solvent may be used alone, or two or more types may be mixed and used.
[0040] In the present invention, it is preferable to use a colloidal silica dispersion in which silica particles are dispersed in the above-mentioned solvent, and the surface treatment can be performed by adding compound (1) to this dispersion and mixing and stirring. The treatment conditions are not particularly limited, but can be, for example, preferably 20 to 150°C, more preferably 25 to 120°C, and preferably 1 to 10 hours, more preferably 1 to 6 hours.
[0041] The amount of compound (1) added is preferably 1 to 50 parts by mass, more preferably 5 to 20 parts by mass, in total, based on 100 parts by mass of the silica particles. Compound (1) can be used alone or in combination of two or more kinds.
[0042] In the surface treatment of the silica particles, an organosilicon compound other than the compound (1), such as an alkoxy group-containing organosilicon compound or a silazane structure-containing compound, may be used in combination. Specific examples of the alkoxy group-containing organosilicon compound include 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, p-styryltrimethoxysilane, and 8-methacryloxyoctyltrimethoxysilane. Specific examples of the silazane structure-containing compound include low-molecular-weight silazane compounds such as 1,1,3,3-tetramethyldisilazane, hexamethyldisilazane, 1,3-divinyl-1,1,3,3-tetramethyldisilazane, octamethyltrisilazane, 1,1,3,3,5,5-hexamethylcyclotrisilazane, and 1,1,3,3,5,5-trimethyltrivinylcyclotrisilazane. These may be used alone or in combination of two or more.
[0043] When an organosilicon compound other than compound (1) is used, it may be added simultaneously with compound (1), or it may be added before or after the surface treatment with compound (1); however, it is preferable to add it after the surface treatment with compound (1). When an organosilicon compound other than the compound (1) is used, the total amount added is preferably 1 to 50 parts by mass, more preferably 5 to 20 parts by mass, per 100 parts by mass of the silica particles.
[0044] After the surface treatment, the solvent is removed by a separation means such as filtration or liquid separation, and the particles are washed and dried to obtain surface-treated silica particles. The drying conditions are not particularly limited, but are preferably 60 to 180°C, more preferably 80 to 150°C, and are preferably 5 minutes to 2 hours, more preferably 10 minutes to 1 hour, for example. The above production method can be similarly applied to inorganic particles and inorganic fillers other than silica particles.
[0045] (3-2) Manufacturing method of surface-treated glass fiber When glass fibers are used as the substrate, glass cloth is particularly preferred. When the surface of the glass cloth is treated, the treatment can be carried out using a glass cloth treatment liquid in which the organosilicon compound of the present invention is dissolved in a solvent containing water. The surface treatment method of the glass cloth is not particularly limited, but specifically, flow coating (immersion method), spin coating, etc. can be mentioned as a method for directly treating the substrate, and other known methods such as spray coating, dip coating, roller coating, brush coating, bar coating, etc. can be appropriately selected and used. After that, it is preferable to perform a heating and drying treatment. As a representative treatment condition, for example, it is preferable to heat and dry at 60 to 180°C, preferably 80 to 150°C for 5 minutes to 2 hours, and to remove the solvent and simultaneously chemically react the organosilicon compound in the solution with the substrate surface. The above manufacturing method can be similarly applied to substrates other than glass cloth.
[0046] [Glass cloth treatment liquid] The glass cloth treatment liquid of the present invention (hereinafter sometimes referred to as "treatment liquid") contains the organosilicon compound of the present invention and water, and the organosilicon compound of the present invention is dissolved in a solvent containing water. From the viewpoint of storage stability and productivity of the treatment liquid, the content of the organosilicon compound is preferably 0.001 to 10.0 mass %, more preferably 0.05 to 5.0 mass %, and more preferably 0.05 to 2.0 mass %, in terms of solid content, relative to the entire treatment liquid.
[0047] The method for producing the glass cloth treatment liquid of the present invention is not particularly limited, and the glass cloth treatment liquid can be produced by adding and dissolving the organosilicon compound of the present invention in a solvent containing water. The temperature when the organosilicon compound is added to the solvent is preferably 10 to 50°C, more preferably 15 to 40°C.
[0048] The glass cloth treatment liquid of the present invention may contain, in addition to the organosilicon compound of the present invention and water, an organic solvent within a range that does not impair the effects of the present invention. The organic solvent is not particularly limited, but is preferably an organic solvent having excellent compatibility with water. Examples of the organic solvent include alcohols such as methanol, ethanol, and isopropanol; ethers such as diethyl ether, tetrahydrofuran, and 1,4-dioxane; esters such as ethyl acetate; and ketones such as acetone and methyl ethyl ketone. One type may be used alone, or two or more types may be used in combination. When an organic solvent is used, its blending amount is not particularly limited, but is preferably 10 to 70% by mass, and more preferably 20 to 60% by mass, of the entire treatment liquid.
[0049] The water contained in the glass cloth treatment liquid of the present invention is preferably adjusted to be acidic from the viewpoint of storage stability. Examples of the acid to be used for adjusting the acidity include organic acids such as formic acid, acetic acid, and citric acid, and inorganic acids such as hydrochloric acid. When an acid is used, the amount of the acid added is preferably 0.001 to 0.5% by mass, more preferably 0.01 to 0.1% by mass, of the total treatment liquid. When an acid is used, the water may be adjusted to be acidic by mixing the acid with water in advance, or the acid may be added to the glass cloth treatment liquid containing the compound (1) to adjust the acidity.
[0050] To the glass cloth treatment liquid of the present invention, an alkoxy group-containing organosilicon compound, a silazane compound, etc. other than the organosilicon compound of the present invention can be added, if necessary, to improve the adhesion and bonding with the glass cloth, within a range that does not impair the effects of the present invention. Specific examples of the alkoxy group-containing organosilicon compound and the silazane compound include the same as those exemplified in the method for producing surface-treated silica particles. In addition, other additives may be added to the glass cloth treatment liquid of the present invention as necessary within the scope of not impairing the effects of the present invention. Specific examples of other additives include water-soluble resins, curing catalysts, physical property adjusters for adjusting the tensile properties of the resulting cured coating, storage stability improvers, surfactants, metal deactivators, antiozonants, lubricants, pigments, etc.
[0051] [Prepreg] The prepreg of the present invention comprises the above-mentioned article and a matrix resin. The article containing the substrate surface-treated with the organosilicon compound of the present invention can be mixed with a matrix resin to form a prepreg. In particular, when the substrate (article) is surface-treated silica particles or surface-treated glass cloth, the resulting prepreg has excellent strength and can be suitably used, for example, for printed wiring boards.
[0052] (1) Goods The article contained in the prepreg is not particularly limited as long as it contains a substrate that has been surface-treated with the organosilicon compound of the present invention, but it is preferable that the substrate itself is a surface-treated substrate, such as surface-treated silica particles or surface-treated glass cloth.
[0053] (2) Matrix resin The matrix resin used in the prepreg of the present invention is not particularly limited and can be appropriately selected from conventionally known resins. Examples of the matrix resin include thermosetting silicone resins, polyimide resins, maleimide resins, epoxy resins, cyanate resins, (meth)acrylic resins, polyphenylene ether resins, and polytetrafluoroethylene resins. Of these, polyphenylene ether resins are preferred.
[0054] Other components can be added to the matrix resin in the present invention in order to accelerate curing of the resin, increase its strength, etc. Specific examples of other components include inorganic fillers, flame retardants, additives, reaction initiators, crosslinking agents, curing agents, organic resins other than the matrix resin, etc. When other components are blended, the amount of the other components added is preferably 1 to 900 parts by mass, more preferably 10 to 500 parts by mass, and even more preferably 10 to 100 parts by mass, relative to 100 parts by mass of the matrix resin.
[0055] (3) Manufacturing method of prepreg The method for producing the prepreg of the present invention is not particularly limited, and general methods for producing glass cloth-containing substrates, films, prepregs, etc. can be applied. For example, a method in which a molten matrix resin or a solution containing a matrix resin is mixed with a surface-treated inorganic filler, and the obtained resin is applied to a glass cloth to impregnate it, or a method in which a matrix resin is applied to a surface-treated glass cloth to impregnate it, etc. can be used.
[0056] (3-1) Method for producing prepreg containing surface-treated silica particles When surface-treated silica particles are used as the article, a prepreg containing the surface-treated silica particles can be obtained by mixing a matrix resin, the surface-treated silica particles, and other components as necessary, and applying the resulting resin or solution to a glass cloth and impregnating it therewith.
[0057] To improve and ensure the coating property, the matrix resin may be diluted with a solvent. Depending on the solubility property of the matrix resin, one organic solvent may be used alone or two or more organic solvents may be used in combination. Examples of organic solvents include alcohols such as methanol, ethanol, isopropanol, and n-butanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; glycol ethers such as ethylene glycol and propylene glycol; aliphatic hydrocarbons such as hexane and heptane; aromatic hydrocarbons such as toluene and xylene; and alkyl ethers such as diethyl ether, diisopropyl ether, and dibutyl ether.
[0058] The method for mixing the matrix resin and the surface-treated silica particles is not particularly limited, but examples include a method in which the matrix resin or a solution containing the matrix resin, the surface-treated silica particles, and other components, if necessary, are mixed by a conventionally known method and stirred for about 10 minutes to 1 hour.
[0059] The amount of the surface-treated silica particles added is preferably 10 to 300 parts by mass, more preferably 50 to 200 parts by mass, and even more preferably 60 to 150 parts by mass, per 100 parts by mass of the matrix resin (the amount of matrix resin contained in the case of a solution). The glass cloth may be surface-untreated or surface-treated, and one type may be used alone or two or more types may be used in combination.
[0060] Next, the matrix resin containing the surface-treated silica particles is applied to the glass cloth and impregnated therein. The prepreg of the present invention can be produced, for example, in accordance with a general method for applying a curable resin composition to glass cloth fibers (coating method). Representative coating methods include direct gravure coater, chamber doctor coater, offset gravure coater, single roll kiss coater, reverse kiss coater, bar coater, reverse roll coater, slotter die coater, air doctor coater, positive rotation roll coater, blade coater, knife coater, impregnation coater, MB coater, MB reverse coater, etc.
[0061] The amount of the matrix resin attached to the glass cloth is preferably 10 to 80% by mass, more preferably 20 to 70% by mass. Within this range, the amount of the matrix resin attached to the glass cloth is appropriate, and there is an effect of improving the adhesion and bonding with the matrix resin, and the strength of the wiring board. If the amount of the matrix resin attached is 10% by mass or more, when the prepreg and the copper foil are laminated to produce a board, the amount of the matrix resin attached to the copper foil is not too small, and sufficient peel strength with the copper foil can be obtained. In addition, if the amount of the matrix resin attached is 80% by mass or less, the amount of the matrix resin is not too large, and resin flow during pressing is unlikely to occur, which is preferable. The amount of the matrix resin attached here indicates the mass % of the matrix resin relative to the mass of the entire prepreg.
[0062] Conditions vary depending on the matrix resin used, but for example, after application, the resin can be dried and then heated at 50 to 300° C. for 1 minute to 24 hours for curing.
[0063] (3-2) Method for manufacturing prepreg containing surface-treated glass cloth When a surface-treated glass cloth is used as the article, a prepreg containing the surface-treated glass cloth can be obtained by mixing a matrix resin or a solution containing the matrix resin and, if necessary, other components, and impregnating the surface-treated glass cloth with the obtained resin or solution. The specific manufacturing method is the same as that in the case of using surface-treated silica particles. Surface-treated silica particles may be added to the matrix resin, and in that case, the amount added is the same as above.
[0064] The thickness of the prepreg of the present invention is not particularly limited, but is preferably 10 to 400 μm, more preferably 30 to 300 μm, and even more preferably 40 to 200 μm. Within this range, for example, when the prepreg of the present invention is used for a printed wiring board, a board such as a copper-clad laminate can be well prepared. The prepreg of the present invention may be semi-cured (B-staged) in advance by heating. There are no particular limitations on the method for B-staging, but for example, the matrix resin may be dissolved in a solvent, impregnated into glass cloth, dried, and then heated at a temperature of 80 to 200°C for 1 to 30 minutes to achieve B-stage.
[0065] [Printed wiring board] The printed wiring board of the present invention is obtained using a prepreg including the article of the present invention. The method for producing the printed wiring board of the present invention is not particularly limited, and a general method for producing a printed wiring board can be applied. A specific example is a method in which the prepreg of the present invention and a copper foil are stacked and pressed, and then heat-cured to produce a substrate as a copper-clad laminate. The method for producing the copper-clad laminate is not particularly limited, and can be produced, for example, by using 1 to 20 sheets, preferably 2 to 10 sheets, of the above prepreg, arranging copper foil on one or both sides of the prepreg, pressing, and then heat-curing.
[0066] The thickness of the copper foil is not particularly limited, but is preferably 3 to 70 μm, more preferably 10 to 50 μm, and even more preferably 15 to 40 μm. Within this range, a multi-layer copper-clad laminate with high reliability can be formed. The molding conditions for the copper-clad laminate are not particularly limited, but for example, it can be molded using a multi-stage press, a multi-stage vacuum press, a continuous molding machine, an autoclave molding machine, or the like, at a temperature of 100 to 400° C., a pressure of 1 to 100 MPa, and a heating time of 0.1 to 4 hours. In addition, the prepreg of the present invention, the copper foil, and the wiring board for the inner layer can be combined and molded to form a copper-clad laminate.
[0067] The method of circuit processing is not particularly limited, and examples thereof include circuit formation processing methods such as drilling, metal plating, etching of metal foil, etc. In addition, a printed wiring board may be produced by a build-up method in which a composition containing a matrix resin or the prepreg of the present invention and copper foil are sequentially laminated. EXAMPLES
[0068] The present invention will be described in more detail below with reference to Synthesis Examples, Examples, and Comparative Examples, but the present invention is not limited to these Examples. In the following formulae, Me represents a methyl group, and Et represents an ethyl group. In the following examples, the kinematic viscosity, specific gravity and refractive index were measured at 25° C., and the parts are parts by mass. In this case, the kinematic viscosity was measured based on JIS Z 8803. The specific gravity was measured based on JIS Z 8804. The refractive index was measured in accordance with JIS K 0062. Nuclear magnetic resonance spectrum ( 1 H-NMR measurements were performed in deuterated chloroform using an AVANCE III / ULTRASIELD 400 manufactured by BRUKER. Infrared absorption (IR) measurements were performed using a Fourier transform infrared spectrophotometer Nicolet 6700 manufactured by Thermo Fisher Scientific.
[0069] [1] Synthesis of organosilicon compounds [Example 1-1] In a 300 mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 100.0 g (hydroxyl value 265 mg KOH / g) of Neoallyl T-20 (trimethylolpropane diallyl ether, manufactured by Osaka Soda Co., Ltd.) and 0.11 g of dioctyltin oxide were placed, and 3-isocyanatopropyltrimethoxysilane was dropped over 1 hour at an internal temperature of 80 to 90°C. At this time, the amount of 3-isocyanatopropyltrimethoxysilane was 1.0 mole relative to the molar amount of hydroxyl groups calculated from the hydroxyl value of Neoallyl T-20. After that, the mixture was stirred at 85°C for 3 hours, and it was confirmed by IR measurement that the absorption peak derived from the isocyanato group of the raw material had completely disappeared, and the reaction was terminated. Then, 7.9 g of silica gel 60N (manufactured by Kanto Chemical Co., Ltd.) was added, and the mixture was stirred at room temperature for 3 hours. After that, the silica gel 60N was filtered off, and the obtained product had a kinetic viscosity of 65.5 mm 2 / s, specific gravity 1.06, refractive index 1.458, pale yellow transparent liquid. 1 It was confirmed by 1 H-NMR that the compound was the organosilicon compound represented by the above formula (2-1). 1 H-NMR (CDCl3, 400MHz) δ:0.56-0.67(m,2H),0.80-0.92(m,3H),1.30-1.52(d,2H),1.53-1.70(m,2H),3.00-3.23(m,2H), 3.25-3.35(m,2H),3.53(s,9H),3.92-3.97(d,2H),4.00(s,2H),4.78-4.95(s,1H),5.05-5.30"(m,4H),5.77-5.95(m,2H)
[0070] [Example 1-2] In a 300 mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 100.0 g (hydroxyl value 237 mg KOH / g) of Neoallyl P-30 (pentaerythritol triallyl ether, manufactured by Osaka Soda Co., Ltd.) and 0.11 g of dioctyltin oxide were placed, and 3-isocyanatopropyltrimethoxysilane was dropped over 1 hour at an internal temperature of 80 to 90 ° C. At this time, the amount of 3-isocyanatopropyltrimethoxysilane was 1.0 mole relative to the molar amount of hydroxyl groups calculated from the hydroxyl value of Neoallyl P-30. After that, the mixture was stirred at 85 ° C. for 3 hours, and it was confirmed by IR measurement that the absorption peak derived from the isocyanato group of the raw material had completely disappeared, and the reaction was terminated. Then, 7.5 g of silica gel 60N (manufactured by Kanto Chemical Co., Ltd.) was added, and the mixture was stirred at room temperature for 3 hours. After that, the silica gel 60N was filtered off, and the obtained product had a kinetic viscosity of 78.2 mm 2 / s, specific gravity 1.07, refractive index 1.462, pale yellow transparent liquid. 1 It was confirmed by 1 H-NMR that the compound was the organosilicon compound represented by the above formula (2-2). 1 H-NMR (CDCl3, 400MHz) δ:0.56-0.70(m,2H),1.52-1.70(m,2H),3.18(s,2H),3.36-3.51(m,6H),3.5 5(s,9H),3.90-4.00(d,6H),4.15(s,2H),4.75-4.95(s,1H),5.05-5.30"(m,6H),5.77-5.95(m,3H)
[0071] [Examples 1-3] In a 300 mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 100.0 g (hydroxyl value 237 mg KOH / g) of Neoallyl P-30 (pentaerythritol triallyl ether, manufactured by Osaka Soda Co., Ltd.) and 0.11 g of dioctyltin oxide were placed, and 3-isocyanatopropyltriethoxysilane was dropped over 1 hour at an internal temperature of 80 to 90 ° C. At this time, the amount of 3-isocyanatopropyltriethoxysilane was 1.0 mole relative to the molar amount of hydroxyl groups calculated from the hydroxyl value of Neoallyl P-30. After that, the mixture was stirred at 85 ° C. for 3 hours, and it was confirmed by IR measurement that the absorption peak derived from the isocyanato group of the raw material had completely disappeared, and the reaction was terminated. After that, 8.2 g of silica gel 60N (manufactured by Kanto Chemical Co., Ltd.) was added, and the mixture was stirred at room temperature for 3 hours. Thereafter, the silica gel 60N was filtered off, and the resulting product had a kinetic viscosity of 55.5 mm 2 / s, specific gravity 1.03, refractive index 1.457, pale yellow transparent liquid. 1 H-NMR confirmed that the compound was the organosilicon compound represented by the above formula (2-3). 1 H-NMR (CDCl3, 400MHz) δ:0.56-0.70(m,2H),1.17-1.28(m,9H),1.52-1.70(m,2H),3.18(s,2H),3.36-3.51(m,6 H),3.78-3.89(m,6H),3.90-4.00(d,6H),4.15(s,2H),4.75-4.95(s,1H),5.05-5.30"(m,6H),5.77-5.95(m,3H)
[0072] [Examples 1-4] In a 500 mL separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 100.0 g (0.581 mol) of Neoallyl E-20 (glycerin diallyl ether, manufactured by Osaka Soda Co., Ltd.) and 0.13 g of dioctyltin oxide were placed, and 119.2 g (0.581 mol) of 3-isocyanatopropyltrimethoxysilane was added dropwise at an internal temperature of 80 to 90°C over 1 hour. The mixture was then stirred at 85°C for 3 hours, and the reaction was terminated when it was confirmed by IR measurement that the absorption peak derived from the isocyanato group of the raw material had completely disappeared. Then, 8.8 g of silica gel 60N (manufactured by Kanto Chemical Co., Ltd.) was added and the mixture was stirred at room temperature for 3 hours. The silica gel 60N was then filtered off, and the resulting product had a kinetic viscosity of 32.0 mm. 2 / s, specific gravity 1.08, refractive index 1.455, pale yellow transparent liquid. 1 It was confirmed by 1 H-NMR that the compound was the organosilicon compound represented by the above formula (3-1). 1 H-NMR (CDCl3, 400MHz) δ:0.56-0.67(m,2H),1.52-1.70(m,2H),3.08-3.23(m,2H),3.54(s,9H) ,3.60-3.70(m,4H),3.95-4.08(m,4H),4.90-4.95(s,1H),4.97-5.05(m,1H),5.10-5.33(m,4H) ,5.82-5.96(m,2H)
[0073] [2] Manufacturing of surface-treated silica particles [Example 2-1] 625 g of silica sol obtained by concentrating a silica concentration of a commercially available acidic aqueous silica sol (trade name: Snowtex O, manufactured by Nissan Chemical Industries, Ltd.) to 40% by mass, and 1125 g of isopropyl alcohol were stirred in a 2-liter glass separable flask equipped with a stirrer, a dropping funnel, a cooling tube, and a thermometer while bubbling air at 25°C. 30 g of the organosilicon compound (2-1) obtained in Example 1-1 was dropped therein, and the temperature was raised to 78°C, and stirring was continued for 4 hours to perform a hydrophobic treatment of the silica sol. Thereafter, the internal temperature was lowered to 70°C, and 34 g of hexamethyldisilazane (trade name: HMDS, manufactured by Shin-Etsu Chemical Co., Ltd.) was dropped, and stirring was performed for 2 hours. The solid was filtered and washed with methanol, and then dried at 110°C under reduced pressure for 1 hour to obtain surface-treated silica particles (A).
[0074] [Example 2-2] Surface-treated silica particles (B) were obtained by the same procedure as in Example 2-1, except that the organosilicon compound (2-1) in Example 2-1 was changed to the organosilicon compound (2-2) obtained in Example 1-2.
[0075] [Example 2-3] Surface-treated silica particles (C) were obtained by the same procedure as in Example 2-1, except that the organosilicon compound (2-1) in Example 2-1 was changed to the organosilicon compound (3-1) obtained in Example 1-3.
[0076] [Comparative Example 2-1] In Example 2-1, the same operation as in Example 2-1 was carried out except that the organosilicon compound (2-1) was changed to 28 g of organosilicon compound (4) (vinyltrimethoxysilane, product name: KBM-1003, manufactured by Shin-Etsu Chemical Co., Ltd.), to obtain surface-treated silica particles (D).
[0077] [3] Manufacturing of prepregs and substrates using surface-treated silica particles [Examples 3-1 to 3-4, Comparative Examples 3-1 to 3-3] A polyphenylene ether resin containing methacryloxy groups as polymerizable reactive groups (Noryl (registered trademark) SA9000 manufactured by SHPP Japan LLC, hereafter referred to as PPE) was mixed with toluene in a mass ratio of 1:1, and the mixed solution was heated and stirred at 80°C for 1 hour to completely dissolve the PPE in the toluene, and then cooled to 25°C to obtain a 50% by mass toluene solution of PPE. Next, according to the compounding ratios (parts by mass) shown in Table 1, a 50% by mass toluene solution of the above PPE (converted to non-volatile content), a crosslinking agent, an organic resin, surface-treated silica particles, and a curing agent were mixed and stirred for 30 minutes to completely dissolve, thereby obtaining a varnish-like curable composition (resin varnish).
[0078] Next, the obtained resin varnish was impregnated into a glass cloth (manufactured by Nitto Boseki Co., Ltd., #1078 type, WEA1078), and then heated and dried at 120° C. for 3 minutes to obtain a prepreg. At this time, the thickness after curing was adjusted to be about 60 μm. Both sides of one of the obtained prepregs were sandwiched between copper foil (GT-MP manufactured by Furukawa Electric Co., Ltd., thickness 12 μm) and laminated, and then sintered under vacuum conditions at 190°C for 90 minutes at a pressure of 40 kgf / cm. 2 By applying heat and pressure under the above conditions, a cured article, evaluation substrate 1, was obtained. In addition, 12 sheets of the prepreg obtained above were stacked, sandwiched between copper foil (GT-MP manufactured by Furukawa Electric Co., Ltd., thickness 12 μm), and laminated under vacuum conditions at 220°C for 90 minutes and a pressure of 40 kgf / cm. 2 By applying heat and pressure under the above conditions, an evaluation substrate 2 was obtained.
[0079] The evaluation substrates 1 and 2 prepared by the above procedure were evaluated by the methods described below. The results are shown in Table 1 below. [Dielectric properties] For each of the evaluation boards 2 produced above from which the copper foil had been removed, the relative dielectric constant and the dielectric loss tangent at 10 GHz were measured by a cavity resonator perturbation method using a network analyzer (E5063-2D5 manufactured by Keysight Corporation). [Copper foil adhesion strength] The peel strength (copper foil adhesion strength) of each of the evaluation boards 1 prepared above was measured by a method conforming to JIS C 6481. At this time, a pattern with a width of 10 mm and a length of 100 mm was formed on a test piece with a width of 20 mm and a length of 100 mm, and the copper foil was peeled off at a speed of 50 mm / min using a tensile tester, and the peel strength (kN / m) at this time was evaluated as the copper foil adhesion strength.
[0080] [Table 1]
[0081] Each component shown in Table 1 will be explained below. PPE: PPO Noryl (registered trademark) SA9000 (polyphenylene ether resin containing methacryloxy groups as polymerizable reactive groups) manufactured by SABIC Innovative Plastics Co., Ltd. (SHPP Japan LLC) Crosslinking agent 1: TAIC (trademark) (triallyl isocyanurate) manufactured by Nippon Kasei Co., Ltd. Crosslinking agent 2: DCP (tricyclodecane dimethanol dimethacrylate) manufactured by Shin-Nakamura Chemical Co., Ltd. Organic resin: Cray Valley Ricon 100 (styrene butadiene random copolymer) Hardener: NOF Corp. Perbutyl P (1,3-bis(butylperoxyisopropyl)benzene, peroxide)
[0082] As shown in Table 1, the printed wiring board having a prepreg using silica particles surface-treated with the organosilicon compound of the present invention has excellent dielectric properties and copper foil adhesion strength.
[0083] [4] Manufacturing of surface-treated glass cloth [Examples 4-1 to 4-3, Comparative Examples 4-1 to 4-5] A glass cloth treatment solution was prepared according to the following procedure, and the glass cloth was subjected to surface treatment. The organosilicon compound (2-1), organosilicon compound (2-2), organosilicon compound (3-1) obtained in Examples 1-1, 1-2, and 1-4 above, and the organosilicon compounds (4) to (6) shown below were each added to a solvent prepared by mixing a 0.1% by mass aqueous solution of acetic acid and methanol in a mass ratio of 50:50, and the solid content concentration was 0.2% by mass. The mixture was stirred to prepare a glass cloth treatment solution. In addition, the following organosilicon compound (7) was added to ion-exchanged water to a concentration of 0.2 mass %, followed by stirring, to prepare a glass cloth treatment liquid containing the following organosilicon compound (7). The obtained glass cloth treatment liquid was added to a silica glass cloth (thickness: 95 μm, mass per unit area: 93 g / m 2 ) and then heated and dried at 110°C for 10 minutes to produce a surface-treated glass cloth.
[0084] Organosilicon compound (4): Vinyltrimethoxysilane (product name: Vinyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.) Organosilicon compound (5): 3-(methacryloyloxy)propyltrimethoxysilane (product name: KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.) Organosilicon compound (6): N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride (trade name: KBM-575, manufactured by Shin-Etsu Chemical Co., Ltd.) Organosilicon compound (7): 3-aminopropyltrimethoxysilane (product name: KBM-903, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0085] The obtained surface-treated glass cloth was evaluated by the following methods, and the results are shown in Table 2 below.
[0086] [Dielectric properties] A rectangular molded piece of 5 cm x 5 cm with a thickness of 0.30 mm was prepared. A network analyzer (Keysight: E5063-2D5) was connected to a strip line (Keycom Co., Ltd.) to measure the dielectric constant and dielectric loss tangent of the molded piece at a frequency of 10 GHz. The measurement results of a glass cloth that was not surface-treated (Comparative Example 4-1) were converted to 100, and evaluation was performed.
[0087] [5] Manufacturing of prepregs and substrates using surface-treated glass cloth [Examples 5-1 to 5-3, Comparative Examples 5-1 to 5-5] The surface-treated glass cloth obtained in Examples 4-1 to 4-3 and Comparative Examples 4-2 to 4-5 was impregnated with a matrix resin (M-1), and the prepreg was obtained by removing the solvent by heating and drying at 100°C for 10 minutes. Next, one prepreg was heat-cured at 180°C for 60 minutes under a pressure of 5 MPa using a vacuum press to produce an evaluation substrate 3. In Comparative Example 5-1, evaluation substrate 3 was produced in the same manner as in the other Examples and Comparative Examples, except that an untreated silica glass cloth was used. Here, the matrix resin (M-1) is a mixture of the above-mentioned PPE, crosslinking agent 1, organic resin, dicumyl peroxide, and toluene in a mass ratio of 75:12.5:12.5:1:70.
[0088] [Dielectric properties] As with the above-mentioned surface-treated glass cloth, the relative dielectric constant and dielectric tangent of each evaluation substrate 3 were measured, and the measurement results of a printed wiring board (Comparative Example 5-1) using a glass cloth that had not been surface-treated (Comparative Example 4-1) were converted to 100 and evaluation was performed.
[0089] [Tensile strength] The tensile strength of the evaluation substrate 3 was measured in accordance with JIS K 6251:2010 using EZ TEST (EZ-L, manufactured by Shimadzu Corporation) under conditions of a test speed of 500 mm / min, a gripping distance of 80 mm, and a gauge length of 40 mm.
[0090] [Solder heat resistance test] Three prepregs obtained above were laminated and heat-cured at 180°C for 60 minutes under a pressure of 5 MPa using a vacuum press to produce evaluation board 4. Each evaluation board 4 obtained was boiled in ion-exchanged water for one hour, and then immersed in a solder bath at 260°C for 30 seconds. The appearance of the board was visually observed, and boards that did not blister were rated as "O" and boards that blistered were rated as "X". The results are shown in Table 2.
[0091] [Table 2]
[0092] As shown in Table 2, the glass cloth treated with the organosilicon compound of the present invention and its cured product (substrate) had low dielectric tangent and excellent tensile strength. On the other hand, the substrate (Comparative Example 5-2) using the glass cloth treated with vinyltrimethoxysilane (Comparative Example 4-2) had poor tensile strength and heat resistance. This is thought to be because the organosilicon compound has a small carbon number and is therefore poorly compatible with the matrix resin. Furthermore, the dielectric tangent of the surface-treated glass cloths of Comparative Examples 4-3 and 4-4 was not sufficiently low, while the dielectric tangent of the surface-treated glass cloth of Comparative Example 4-5 was high, resulting in low heat resistance of the substrate using the same (Comparative Example 5-5).
Claims
1. An organosilicon compound represented by the following formula (1): 【Chemistry 1】 (In the formula, Me represents a methyl group, R 1 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms; R 2 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms; R 3 represents a hydrogen atom or a methyl group, X represents a p+q+1 valent hydrocarbon group having 3 to 20 carbon atoms, including a branched structure or a ring structure, m represents an integer of 1 to 3, n represents an integer of 1 to 12, p is 0 or 1, q represents an integer of 1 to 3, and p+q represents an integer of 1 to 4.
2. 2. The organosilicon compound according to claim 1, which is represented by the following formula (2) or (3): 【Chemistry 2】 (In the formula, Me, R 1 , R 2 , m and n are the same as above, and R 4 represents a hydrogen atom, a methyl group, or an allyloxy group.
3. R 1 is a hydrogen atom, a methyl group, or an ethyl group, and R 2 3. The organosilicon compound according to claim 2, wherein is a hydrogen atom and n is 3.
4. An article comprising a substrate surface-treated with the organosilicon compound according to any one of claims 1 to 3.
5. 5. The article of claim 4, wherein the substrate is an inorganic material.
6. 6. The article of claim 5, wherein the inorganic material is silica particles or glass fibers.
7. A prepreg comprising the article of claim 4 and a matrix resin.
8. A printed wiring board comprising the prepreg according to claim 7.
9. 4. A glass cloth treatment liquid comprising the organosilicon compound according to claim 1 dissolved in a solvent containing water.
Citation Information
Patent Citations
Thermosetting alkoxysilyl compound having two or more alkoxysilyl groups, composition containing same, cured product, use thereof, and method for producing alkoxysilyl compound
JP2018500309A
Adhesive for bonding liquid silicone rubber
WO2017100750A1
Glass cloth, prepreg and printed wiring board
JP2018127747A
High frequency thermosetting resin composition, prepreg, laminated sheet, and printed circuit board using the same
JP6684822B2
Surface-treated glass cloth, prepreg, and printed wiring board
WO2020194772A1